El derecho a la educación y a la salud en la vida cotidiana infantil en situación de riesgo humanitario - Eyng, Ana Maria; Pimpão Ferreira, Bárbara; Morais Tosta, Priscila; Gomes Alves Mörking, Tiago (Universidad de Costa Rica, 2024)
This article analyzes the risks to children's rights, with an emphasis on education and health in humanitarian situations circumscribed by child poverty, combined with the pandemic health crisis. The argument was based on the question: according to the students' perception what are the impacts of the pandemic and the post-pandemic period on education and health? Therefore, the objective of the study was to map students’ perceptions of their Rights in their daily lives, in six different Latin American countries. Empirical data were obtained through online forms (with open and closed questions) via Google Forms applied in two stages of qualitative research carried out in the second half of 2020 and 2022. The first stage covered 504 basic education students (10-18 years old) from eight educational institutions and the second 462 of thirteen institutions also from basic education. Thus, the contributions of 966 students are discussed in this text in dialogue with bibliographic and documentary references. Closed questions were statistically systematized and content analysis was applied to open questions (Bardin, 2009), as a whole, the data is analyzed using a qualitative approach. Students highlight the right to education and health as the most priority when speaking out about the Rights necessary in their daily lives. Such perceptions reveal specificities of educational communities and the challenges experienced in guaranteeing Rights in everyday spaces which affect the processes of access, permanence and results of education, as well as physical and emotional health problems which emerged and/or worsened during the period. Therefore, in this context the risks increased and worsened in a scenario in which a historical weakness in guaranteeing children's rights was already identified, especially regarding the rights to education and health.